2014
DOI: 10.1097/ans.0000000000000030
|View full text |Cite
|
Sign up to set email alerts
|

Borders, Centers, and Margins

Abstract: Nurses in North America have a distinguished history of involvement in immigrant health due to the immigrant character of this region. The Western Hemisphere is a region composed of recent migrants from nearly every corner of the globe. Complicated economic, environmental, and social dynamics contribute to these various migration patterns and commensurate health-related issues-physical, psychological, and spiritual. Nurses attuned to health issues of newer immigrants' lives use newfound knowledge to shape the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The SNs identified the credible fear of undocumentedness (i.e., lack of birth certificate or citizenship) creates a barrier to accessing healthcare in general and mental healthcare in particular, underscoring the critical need for education on health and guidance for access to services (Hilfinger Messias et al, 2015;McGuire, 2014). McGuire (2014) has suggested that the social construction of undocumentedness may be regarded as a kind of violence toward the immigrant because of the marginalization, trauma and suffering it creates. SNs offer a safe haven for the provision of services to newly arrived children, and by extension, they may have the opportunities to help immigrant parents and immigrant communities overall (Capps et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The SNs identified the credible fear of undocumentedness (i.e., lack of birth certificate or citizenship) creates a barrier to accessing healthcare in general and mental healthcare in particular, underscoring the critical need for education on health and guidance for access to services (Hilfinger Messias et al, 2015;McGuire, 2014). McGuire (2014) has suggested that the social construction of undocumentedness may be regarded as a kind of violence toward the immigrant because of the marginalization, trauma and suffering it creates. SNs offer a safe haven for the provision of services to newly arrived children, and by extension, they may have the opportunities to help immigrant parents and immigrant communities overall (Capps et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Whitty-Rogers et al (2016) exposed that all other things being equal, the ethnic minority is afflicted with diabetes three to five time more than the general population. Mcguire (2014) posits that one of the major contributory factors of hegemony is the existence of neoliberal policies. As an economic policy, neoliberalism promotes deregulation, privatization, and diminishing social spending of the government.…”
Section: Description Of the Theorymentioning
confidence: 99%